The Impact of Neocolonialism on India's COVID-19 Response. Issue 1 (17th May 2022) - Shah, Dhruv M.; Kulkarni, Mrunmayi; Mathur, Poonam
In this paper, we analyze the impact of COVID-19 in India and the nation's shortcomings in responding appropriately to the pandemic. We discuss how international vaccine inequities, rooted in neocolonialism, and the WHO's broad recommendation of Global North pandemic responses (i.e., lockdowns, nonspecific social distancing) blunted the effectiveness of India's COVID-19 response and instead heightened classism, economic turmoil, and unnecessary infection and death from the virus.